Adams's outline of orthopaedics - Hamblen, David L. (Elsevier Churchill Livingstone, 2010)
This extensively revised and redesigned edition of Adams's classic textbook on orthopaedics celebrates its 50th year in print. Renown for its clear, comprehensive and concise account of the subject the book will appeal to undergraduate, postgraduate and trainee surgeons alike.